2020
DOI: 10.1038/s41467-020-17649-9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-rich stars with unusual abundances are challenging theoretical predictions

Abstract: Almost all chemical elements have been made by nucleosynthetic reactions in various kind of stars and have been accumulated along our cosmic history. Among those elements, the origin of phosphorus is of extreme interest because it is known to be essential for life such as we know on Earth. However, current models of (Galactic) chemical evolution under-predict the phosphorus we observe in our Solar System. Here we report the discovery of 15 phosphorusrich stars with unusual overabundances of O, Mg, Si, Al, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…Possible solutions of the Ba puzzle, both from the spectra and the nucleosynthesis prospective, are still under investigation. Masseron et al (2020b) reported anomalous Ba enhancements (ten times higher than the other s-process elements) in stars that are also anomalous in the lighter elements, specifically those rich in P (Masseron et al 2020a). As discussed above, this pattern cannot be reproduced by an s-process model because of the nuclear properties of the isotopes involved.…”
Section: Discussionmentioning
confidence: 97%
“…Possible solutions of the Ba puzzle, both from the spectra and the nucleosynthesis prospective, are still under investigation. Masseron et al (2020b) reported anomalous Ba enhancements (ten times higher than the other s-process elements) in stars that are also anomalous in the lighter elements, specifically those rich in P (Masseron et al 2020a). As discussed above, this pattern cannot be reproduced by an s-process model because of the nuclear properties of the isotopes involved.…”
Section: Discussionmentioning
confidence: 97%
“…However, this star does not show Na enhancement, and the Si enhancement seen here does not appear in our ω Cen stars (see Figure 22 below), though enhanced Si is found in a population of field stars in the inner halo (dubbed "Jurassic";Fernández-Trincado et al 2019b, which may arise from tidally disrupted globular clusters. Intriguingly, Masseron et al (2020a) identified 2M18120031-1350169 as one of 15 APOGEE stars with extreme P enhancement, finding [P/Fe]=1.65 using a custom analysis of the APOGEE spectrum (rather than the ASP-CAP abundance). The unusually high [X/Fe] values for Mg, O, Si, and Al are also found in the other members of this P-rich population (see Figure 9 of Masseron et al 2020a), and the high [Ce/Fe] accords with the enhanced s-process abundances found in follow-up optical spectroscopy by Masseron et al (2020b).…”
Section: High-χ 2 Starsmentioning
confidence: 99%
“…Intriguingly, Masseron et al (2020a) identified 2M18120031-1350169 as one of 15 APOGEE stars with extreme P enhancement, finding [P/Fe]=1.65 using a custom analysis of the APOGEE spectrum (rather than the ASP-CAP abundance). The unusually high [X/Fe] values for Mg, O, Si, and Al are also found in the other members of this P-rich population (see Figure 9 of Masseron et al 2020a), and the high [Ce/Fe] accords with the enhanced s-process abundances found in follow-up optical spectroscopy by Masseron et al (2020b). From the overall abundance patterns, Masseron et al (2020a,b) argue that the chemical peculiarities of these stars do not originate in globular clusters or binary mass transfer, and they are a challenge to explain with existing stellar nucleosynthesis models.…”
Section: High-χ 2 Starsmentioning
confidence: 99%
“…(v) For our selection, we also disregarded stars in GCs from our sample, i.e., those sources analyzed in Masseron et al (2019) and Mészáros et al (2020b). (vi) Lastly, field stars identified previously as P-, N-and Si-rich stars from Martell et al (2016), Fernández-Trincado et al (2016a), Fernández-Trincado et al (2017, 2019d, and Masseron et al (2020) were excluded from our sample.…”
Section: Datamentioning
confidence: 99%
“…The search for field stars that were born in GCs (Lind et al 2015;Martell et al 2016;Fernández-Trincado et al 2015a, 2016b, 2019d,c,b,a, 2020cSimpson et al 2020) is one clear example of the power of chemical tagging. This is possible because GCs appear to be the only environment responsible for the presence of light-element anti-correlations at all stellar evolutionary phases (e.g., Martell et al 2016;Pancino et al 2017;Bastian & Lardo 2018;Masseron et al 2019;Mészáros et al 2020a), unless they are part of a binary system (Bastian & Lardo 2018;Fernández-Trincado et al 2019c), or part of the new kind of recently discovered anomalous Phosphorus-rich field stars (see, e.g., Masseron et al 2020). Thus, a complete census of all those chemically anomalous stars will help develop a better understanding for the assembly of the inner and outer halo, where substantial amount of stellar debris from GCs are thought to currently reside (see, e.g., Martell et al 2016;Fernández-Trincado et al 2019b,a, 2020c.…”
Section: Introductionmentioning
confidence: 99%